DESKRIPSI PRODUKSI TANDAN BUAH SEGAR (TBS) KELAPA SAWIT PLASMA BINAAN PT. SANDABI INDAH LESTARI DI DESA TABA TEMBILANG - Iin Novalinda; Endah Heryanti (UNIVED Press, 2018)
This research is to find out the effect of the capital, labor and the land area toward palm fruit plasma binaan PT. Sandabi Indah Lestari Taba Tembilang Village. This research used descriptive quantitative, to describe one situation. The researcher used observation and questioner tooo collecting the data.To find out the effect of capital, labor and the land area toward palm fruit plasma PT. Sandabi Indah Lestari Taba Tembilang Village. The researcher used linier berganda analysis. This method used to quantify more than two variable independan and variable dependen.From the calculation to describe the effect of the capital, labor and the land area toward palm fruit plasma PT. Sandabi Indah Lestari Taba Tembilang Village. Can be seen from the R value which shows the relationship betwen capital variable, labor, the land area toward palm fruit, the magnitude of the relationship is 0,843 or 84,3%.While the coefficient of multiple detemination (R) or R square shows the coefficient of determination 0,711 or 71,1% this percentage shows that capital variable, labor and the land of area can contribute to palm fruit production by 71,1%, and the remaining 28,9% influenced by other variable which are not included in this research.